Pelaksanaan Perjanjian Kredit Dengan Jaminan Fidusia Pada PT. Pegadaian (persero) Kantor Wilayah I Medan - Alexander Johannes M Simanjuntak (Recital Review, 2021)
Abstract The high demand of public for installment plans with fiduciary security has changed PT. Pegadaian (Persero), a state-owned enterprise which business was initially about auction launches a financing product i.e. KREASI (Installment Plans with Fiduciary System). However, in practice, the implementation of this product is different form Law No. 42/1999 on Fiduciary Security. This is the background of this research. This research is conducted to discover how the agreement of Installment Plans with Fiduciary System is implemented and executed in PT. Pegadaian (Persero) Regional Office 1 Medan and why it is implemented differently from what is regulated in Law on Fiduciary Security.This is a normative juridical research which uses secondary data consisting of primary, secondary and tertiary legal materials. This research is descriptive analytical. The instrument used to collect the data consist of library research and field research at the PT. Pegadaian (Persero), Regional Office 1 Medan.The research result demonstrate that fiduciary security in its execution is not registered in consensus way in which defaulted debtors are given an opportunity to sell their collateral by themselves (motorcycles or cars) and if they are not willing to have consensus, they can take legal way through a court. The implementation of Regulations of Directors of PT. Pegadaian Number 67/DIR.I/2016 dated September, 2016 on Technical Guidance to online KREASI contradicts the provisions stipulated in Law No. 42/1999 on Fiduciary Security because it differently implements Article 5 paragraph (1) and Article 11 paragraph (1), in which some installment plans which is implemented by using underhanded letter and by not registering it do not provide any legal certainty in its execution in case of debtors’ default (Article 15 and 29) and may harm state finance. It is suggested that regulation of Directors of PT. Pegadaian on Installment Plans with Fiduciary System be revised and fully adjusted to the Law No. 42/1999 on Fiduciary System and that small installment plans be implemented by using auction security.   Keywords: Credit Agreement, Fiduciary Security